Hubungan antara Sikap Kepedulian Lingkungan dan Perilaku Pro Lingkungan pada Produser Ikan Pindang di Desa Tanjungsari, Kendal, Jawa Tengah - Elyza Alvinna Mu’arif Mu’arif; Femmy Lekahena (LPPM Universitas Proklamasi 45, 2024)
ABSTRACT Fish salting producers are faced with the challenge of managing waste generated from the production process. This production activity, which produces waste, can affect the local environmental conditions. This study aims to empirically prove the relationship between environmental concern attitudes and pro-environmental behaviors among fish salting producers in Tanjungsari Village, Kendal, Central Java. A total of 80 fish salting producers in Tanjungsari Village were sampled using the convenience sampling technique. The results found a Pearson product moment correlation coefficient of 0.456 (p<0.01). This means that there is a positive and very significant relationship between environmental concern attitudes and pro-environmental behaviors. Keywords: Environmental Concern Attitudes, Pro-Environmental Behaviors, Fish Salting